2018
DOI: 10.1155/2018/8936108
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Inhibitory Effect of Gujin Xiaoliu Tang in Non‐Small Cell Lung Cancer

Abstract: Non-small cell lung cancer (NSCLC) is a serious threat to people's health. This study aims to determine the possible effect of Gujin Xiaoliu Tang (GJXLT) on NSCLC, which is an empirical formula from Professor Dai-Han Zhou. In this study, chromatographic fingerprinting of GJXLT and A549 cell model in vitro and in vivo was established. We cultured A549 cells in vitro and found that GJXLT inhibited A549 cell growth and induced apoptosis. Compared with the control group, the expression of p-STAT3 and VEGF proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Traditional Chinese Medicine (TCM) has been shown to have efficacy in improving life quality and prolonging the survival time in cancer patients [ 14 , 15 ], and enhancing the response of radiotherapy, chemotherapy, targeted therapy and photodynamic therapy to cancer [ 16 20 ]. Huang Lian Jie Du Decoction (HLJD, Oren-gedoku-to in Japanese, Hwangryunhaedok-tang in Korean), a classical TCM formula with anti-inflammatory effects, has been widely used as combination therapy for cancer [ 21 , 22 ], arthritis [ 23 ], cerebral ischemia/reperfusion [ 24 , 25 ], type II diabetes [ 26 , 27 ], and atopic dermatitis [ 28 ] in China [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese Medicine (TCM) has been shown to have efficacy in improving life quality and prolonging the survival time in cancer patients [ 14 , 15 ], and enhancing the response of radiotherapy, chemotherapy, targeted therapy and photodynamic therapy to cancer [ 16 20 ]. Huang Lian Jie Du Decoction (HLJD, Oren-gedoku-to in Japanese, Hwangryunhaedok-tang in Korean), a classical TCM formula with anti-inflammatory effects, has been widely used as combination therapy for cancer [ 21 , 22 ], arthritis [ 23 ], cerebral ischemia/reperfusion [ 24 , 25 ], type II diabetes [ 26 , 27 ], and atopic dermatitis [ 28 ] in China [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) in combination with chemotherapy is routinely recommended for patients with NSCLC which acts as therapeutic effect through regulation of multiple compounds, targets, and pathways [11,12]. In addition, TCM can not only relieve chemotherapy-related side effect but also prolong the survival time of patients [13].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of clinical studies have demonstrated that TCM can be combined with surgery, radiotherapy and chemotherapy to achieve better results, prevent tumor progression, alleviate clinical symptoms and reduce adverse reactions of radiotherapy and chemotherapy, thereby improving the quality of life and prognosis of patients ( The Lancet Oncology, 2015 ). For example, Xiaoliu decoction (XLD) has been widely used in China and achieved definite curative effects in colorectal cancer, liver cancer, pancreatic cancer, non-small cell lung cancer and glioma ( Fu and Xia, 2004 ; Wang et al, 2004 ; Hou et al, 2018 ). The recommended formula mainly includes Baihuasheshecao (15 g), baizhi (10 g), Baizhu (15 g), banxia (10 g), Banzhilian (15 g), chenpi (10 g), Chuanxiong (10 g), Danshen (15 g), Fuling (15 g), Gancao (6 g), Gouteng (10 g) and Yanhusuo (10 g).…”
Section: Introductionmentioning
confidence: 99%